Evaluating Opportunities to Implement Hospital-Based Health Technology Assessment (HB-HTA) in Selected Hospitals in the Kraków Municipality - Dusza, Dominika; Furman, Maciej; Gałązka-Sobotka, Małgorzata; Kowalska-Bobko, Iwona (Journal of Public Governance, 2021)
Objectives: Hospitals are the entry point for newly implemented innovative health technologies. Hospital-based health technology assessment (HB-HTA) has been developed to facilitate the use of new health technologies in hospitals. The purpose of this study was to evaluate opportunities to implement HB-HTA in selected hospitals located in the Kraków municipality in Poland.Research Design & Method: We used shortened version of a questionnaire from a project called “Implementation of the Hospital-Based HTA (HB-HTA) – Hospital Assessment of Innovative Medical Technologies”. The participants were hospital managers working in three hospitals located in Kraków: the Ujastek Medical Centre Limited Liability Company (LLC), the Brothers Hospitallers of Saint John of God Hospital LLC, and the University Hospital in Kraków. The survey was conducted and made available online.Findings: Each of the participating hospitals had implemented new medical technologies. Applications for the implementation of innovative medical technology had been considered by the hospital directors; however, departmental heads were required to act as the lead applicants. Two out of these three hospitals had developed both an application template for the implementation of innovative technologies and a formalized path for their examination. The main source of financing new technologies is the hospitals’ funds. Before implementing the technology, hospitals had consulted the following agencies: the National Health Fund, the Ministry of Health, medical technology manufacturers or producer organisations, medical voivodeship consultants, and other hospitals. The financial consequences of the medical technologies implementation were analyzed.Implications / Recommendations: The hospitals define innovative medical technologies in a correct way. There are no separate HTA units in any of the hospitals. The surveyed hospitals have the capability to implement HB-HTA.Contribution / Value Added: The implementation of HB-HTA processes in the analysed hospitals may require the hospital managers to broaden knowledge about this area. The implementation of HB-HTA procedures in hospitals may have positive economic effects on the entire health care system.Article classification: pilot studyJEL classification: D25, H41, O22, R1